2002
DOI: 10.1620/tjem.197.87
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Localization of Aquaporin 4 and .ALPHA.1-Syntrophin in the Vascular Feet of Brain Astrocytes.

Abstract: Aquaporin 4 (AQP4) is a recently discovered membrane bound water-selective channel and has been described at the light microscopic level to be predominantly expressed in the astrocytes of the brain, especially at the perivascular astrocyte endfoot processes. Alpha1-syntrophin, a member of dystrophin-associated protein, has also been reported at the light microscopic to be expressed level in the same site of astrocytes as AQP4 and interacts with other molecules through its PDZ domain. AQP4 expression has been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…This suggestion was further substantiated by recent studies of brain microvessels in mdx mice (Inoue et al 2002;Nico et al 2003Nico et al , 2004, showing that both endothelial and glial cells were altered, suggesting changes in vascular permeability, i.e., breakdown of the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 64%
“…This suggestion was further substantiated by recent studies of brain microvessels in mdx mice (Inoue et al 2002;Nico et al 2003Nico et al , 2004, showing that both endothelial and glial cells were altered, suggesting changes in vascular permeability, i.e., breakdown of the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 64%
“…These two channels plus a-syntrophin and other DGC members also aggregate in glia when presented with laminin in cell culture (Guadagno and Moukhles, 2004). In addition, immunolocalization studies have shown that Kir4.1 and AQP4 are tightly co-localized in rat retina (Nagelhus et al, 1999), and AQP4 localization in astrocytes appears to be highly dependent on a-syntroin (Inoue et al, 2002). Direct interactions between AQP4, a-syntrophin, Dp71 and b-dystroglycan have been shown by IP assays (Neely et al, 2001;Amiry-Moghaddam et al, 2003a,b).…”
Section: Discussionmentioning
confidence: 98%
“…In the brain, they are mainly expressed in perivascular astrocytes and in choroid plexuses, suggesting a potential role in water homeostasis, regulation of transport mechanisms across BBB and cerebrospinal fluid production. 7,10,19,31,39,44 Mutations of DAPs are involved in muscular dystrophy, 45 and are responsible for structural and biochemical changes in the brain. 46 The dystrophin isoform Dp71 is localized in the perivascular glial endfeet, in which it is involved in BBB maturation 39,47 and in the clustering of the AQP4 water channel on the astrocyte glial membranes.…”
Section: Discussionmentioning
confidence: 99%